Piet Mondrian, early Neo-Plastic compositions, and six principles of Neo-Plasticism - Fallahzadeh, Ali; Yousof, Ghulam Sarwar (2019)
In spite of the prominent role of Piet Mondrian (1872-1944) as a pure abstract painter and writer of his theories who developed the abstract art into what he called Neo-Plasticism, little has been written about him compared to other painters such as Picasso and Matisse. Examining the past and recent literature published about Mondrian, some scholars examined the aesthetic evolution of Mondrian’s vision toward his Neo-Plastic art and theory within a historical context by depending on the influences he received from circle of thinkers, artists, and friends during his life. While other scholars analyzed the components of Neo-Plastic theory through formal tenets of De Stijl or a metaphysical lens through premises of western philosophies such as Theosophy, Hegel, and Platonism. Nevertheless, despite the emphasis of the majority of scholars on close relation between Mondrian’s paintings and writings, researchers showed little tendency to examine the development of core formal theories of Neo-Plasticism through a parallel analysis of his Neo-Plastic paintings and his theoretical writings. Therefore, in this paper I aim to examine Mondrian’s early artistic ideas, through a coinciding analysis of his 1919-1920 paintings and his 1919-1923 theoretical essays. In this article, I have considered six principles of Neo-Plasticism published in 1926 by Mondrian, as my main point of departure. The main objective of this paper is to reveal the degrees of Mondrian’s awareness toward his refined, crystalized, aesthetic principles - he wrote in 1926 - by examining his early Neo-Plastic 1919-1920 compositions and his 1919-1923 theoretical essays. By conducting a context independent research on Mondrian’s paintings and writings, I aim to propose a novel perspective looking through the very core theory of Neo-Plasticism and to motivate more scholars to examine Mondrian’s Neo-Plastic paintings and writings as integrated body of his Neo-Plasticism.